Evaluating Nodulation and its Effects on Some Agromorphological Parameters of Soybean Varieties (Glycine max L.) - N'Zi, J C; Koua, A P; Kahia, J; Kouassi, K D; N'guetta, A S P; Kouame, C (Asian journal of plant sciences, 2016)
Recent survey in the Soubre region of Cote d'Ivoire has showed high soil fertility depletion. The cost of mineral fertilizer is high and does not always yield a positive return on investment. Soybean can use atmospheric nitrogen through biological fixation by establishing a symbiotic relationship with Rhizobium bacteria. Nitrogen (N) is subject to intense chemical and microbiological transformation processes and is, therefore a very mobile nutrient element in the soil-plant-atmosphere continuum. A study was conducted at Logboayo and Soubre to evaluate the effect of IRAT-FA3 Bradyrhizobium japonicum strain inoculum on the nodulation and some growth parameters of five soybean varieties (Glycine max) named Canarana, Doko, V3-2013, V6-2013 and IT-235. A randomized complete block design with a split plot replicated three times was used. Inoculation was the main factor and variety the subplot treatment. Data were collected on seedling emergence, growth parameters and nodulation. Results showed that lowest emergence time of 6.49 Days After Sowing (DAS) was recorded at Soubre compared to 6.91 DAS for Logboayo. Doko variety had the highest number (11) of nodules per plant in inoculated treatments. The variety V3-2013 showed ability to nodulation with indigenous rhizobia. Seeds inoculation resulted in an increase of nodules and growth of organs. The results of the present study opens up option for soybean to be grown along other crops in order to address soil fertility problems in the project area.